HUBUNGAN DUKUNGAN KELUARGA DENGAN SELF EFFICACY IBU ANAK AUTIS - rahmadani, elsi (Jurnal Kesehatan Saintika Meditory, 2025)
Children with autism are children with developmental disorders characterized by limited and repetitive activities or interests, as well as challenges in social interaction and communication. The purpose of this study was to analyze the relationship between family support and maternal self-efficacy of mothers who have autistic children at SLB Negeri in Bengkulu. This study is a type of quantitative correlation research with a cross-sectional analysis design. The sample in this study was 43 respondents of mothers who had autistic children at SLB Negeri Bengkulu with a purposive sampling technique. Data collection used a family support and maternal self-efficacy questionnaire and data analysis used the Chi-Square test. The results showed that 51.2% of respondents had less family support and (51.2%) had high self-efficacy in mothers with autistic children at SLB Negeri Bengkulu. The results of the Chi-Square statistical test showed p = 0.001 <0.05. The conclusion is that there is a relationship between family support and maternal self-efficacy of mothers of autistic children at SLB Negeri Bengkulu. It is expected that families can provide and improve good support for mothers who have autistic children by providing informational, emotional, assessment, and instrumental support. Keywords: Family Support, maternal self-efficacy, autistic children